Internet connectivity disruption in Congo (Congo) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Congo. Data sourced from IODA.
Network Disruption Incident ID: CG-2026-0012. Severity: critical. Confidence: 67%